Establishing the effect of COVID-19 lockdown policy on the utilization of facility-based delivery in Kenya: a multi-method study - Kuloba, MaryBennah; Strupat, Christoph; Aye, Thit Thit; Wamalwa, Phidelis; Gichuki, Judy; Tsofa, Benjamin; De Allegri, Manuela (BMC health services research, 2025)
Background: Amidst the COVID-19 pandemic, lockdown policies emerged as pivotal policies to contain viral transmission. Questions arise about whether their implementation challenged access to care, particularly in regions with fragile health systems, such as sub-Saharan Africa. Robust evidence on the effect of lockdown policies on access to healthcare services is sparse, also due to a lack of suitable data. We addressed this knowledge gap and assessed the effect of the COVID-19 lockdown policy on facility-based delivery during the first wave of the pandemic in Kenya. Methods: We triangulated results from two parallel yet independent quantitative analyses, exploiting the fact that COVID-19 lockdown policies in Kenya were implemented only in some counties. First, we relied on nationally representative repeated cross-sectional population-based surveys conducted in 2018 and 2020, with data being analyzed using a pre-post study with control. Second, we used monthly data from the Kenya Health Information System (from January 2019 to November 2020) to construct an interrupted time series (ITS) with independent controls, setting April 2020 as the interruption month (i.e., the onset of the lockdowns). Results: The controlled pre-post-analysis detected no significant effect of the lockdown policy on facility-based delivery in lockdown counties compared with non-lockdown counties. The ITSA model showed that the lockdown counties experienced an immediate increase of 4.97% (CI: 0.51%, 9.43%) in facility-based delivery compared with the non-lockdown counties during the first wave of the pandemic. This was followed by a significant monthly decrease of 0.97% (CI: -1.60%, -0.34%) compared with non-lockdown counties. Conclusion: We found no overall effect of the lockdown policy on facility-based deliveries. Our findings suggest that when managed effectively, lockdowns do not disrupt access to maternal health services. Our findings highlight the importance of implementing context-specific strategies to safeguard maternal healthcare during public health crises. Future research should explore localized and socioeconomic differences in how populations respond to public health interventions during pandemics.
Gesehen am 01.12.2025
Keywords: Kenia